Six species of Calyptotheca (Bryozoa, Cheilostomata, Lanceoporidae) from the Gulf of Carpentaria and northern Australia, with description of a new species - Cumming, Robyn L.; Tilbrook, Kevin J. (Zootaxa, 2014)
A new diagnosis is presented for Calyptotheca Harmer, 1957 and six species are described from the Gulf of Carpentaria: C. wasinensis (Waters, 1913) (type species), C. australis (Haswell, 1880), C. conica Cook, 1965 (with a redescription of the holotype), C. tenuata Harmer, 1957, C. triquetra (Harmer, 1957) and C. lardil n. sp. These are the first records of Bryozoa from the Gulf of Carpentaria, and the first Australian records for C. wasinensis, C. tenuata and C. triquetra. The limit of distribution of three species is extended east to the Gulf of Carpentaria, from Kenya for C. wasinensis, from China for C. tenuata, and from northwestern Australia for C. conica. The number of tropical Calyptotheca species in Australian territorial waters is increased from seven to eleven.